Rerouting the worlding of inter-ethnic estrangement through critical solace: Shivani Sivagurunathan’s Yalpanam - Shanthini Pillai,; Jeslyn Sharnita Amarasekera,; Wong, Angeline Wei Wei (Penerbit Universiti Kebangsaan Malaysia, 2023)
Notes of estrangement and exile, flight and peregrination are themes that are often closely threaded into the narratives of contemporary Malaysian novelists. This is especially so for those writers who live abroad but are continually drawn back across the sea of memory to draw on key episodes that have been the catalyst for the creation of the Malaysian diaspora. References to the racial riots of 1969 are foremost among these, with the Japanese Occupation a close second. We suggest that these have created an emerging empire of transnational narratives that has worlded Malaysia through the spectres of national trauma until many forget the very act of fictional worlding. In this paper, we interrogate the interior realities of home-based writings by choosing the novel Yalpanam (2021) by Shivani Sivagurunathan. We argue that the descriptive poetics of its narrative reworlds melancholy, trauma and shame through the interweaving of inter-ethnic and intergenerational perspectives. Taking centrestage is Yalpanam, the house from which the novel derives its very title that plays a significant role in rerouting the trajectory of inter-ethnic estrangement through an integration of solace and healing as part of the narrative’s rhetorical strategy. This trajectory unfolds in the novel through a bricolage of the legacies of the past that form the inner sanctum of the novel, integrating the micro-narratives of letters, folk memory, family stories and formalised historical events. We suggest that these micro-narratives are collectively restorative and recuperative. It is through the commingling of these micro narratives that the novel presents what we see as a re-worlding of transnational aesthetics of estrangement that eventually engenders a sense of solidarity through intertwined ethno-memories.